Tailor-made compostable polyurethanes. Issue 5 (5th January 2022) - Hu, Pin; Kumar, Anil; Gharibi, Reza; Agarwal, Seema
Abstract : Designed polyurethanes with degradable ester units all throughout the polymer backbone and quaternized ammonium units in the hard segment (tensile strength ∼30 MPa, elongation at break ∼1400%) show degradation in 35 days in industrial compost. Abstract : The basic design principle for making polyurethanes recyclable and their waste management are highly relevant in light of increasing concerns about plastic pollution and the occurrence of microplastics in the environment. Since polyurethanes are used with different property profiles for various applications in different sectors, tailor-made structures are required to undergo different types of recycling and waste management according to the situation. Fast and completely degradable polyurethanes under compost are prepared in this work with degradable ester units in both soft and hard segments by a polyaddition reaction and structurally characterized by nuclear magnetic resonance spectroscopy (NMR). The polyurethanes are mechanically strong: the tensile strength is around 30 MPa, and the elongation at break is ∼1400%. The polyurethanes have tertiary ammonium and quaternized tertiary ammonium units in their side chains that modulate the crystallinity and polarity for fast degradation. An almost quantitative degradation in compost was observed at 45 °C in 3 months, whereas at 58 °C, the temperature specified by ASTM D6400, complete degradation took only 35 days which is much faster than the known compostable polymers.